Correlation analysis of Carbon Dioxide, Oxygen, Temperature and Humidity of Yadavaran Oil field in Khuzestan province - Mohammad velayatzadeh; Sina Davazdah Emami; Zahra Naserzadeh (Mashhad University of Medical Sciences, 2018)
Background & Objective:Emission of Carbon dioxide in the atmosphere has an important role in increasing temperatures and, its higher concentration can effect on human health. Due to this issue, this study is aimed to measure the amount of the released carbon dioxide into the atmosphere in different part of Yadavaran Oil field and compare with international standards in 2017. Material & Methods:The present investigation was accomplished in Yadavaran oil field of Khuzestan province of Iran in 2017. In this study measurement of parameters including carbon dioxide, carbon monoxide, oxygen, relative humidity and temperature was done in 64 stations with 3 replications using ALTAIR 4X and Trotec BZ30. Data was analyzed by one-way ANOVA and Kolmogorov-Smirnov tests. Moreover, Correlation analysis was performed using Pearson and Spearman coefficients. Results:The results showed that concentration range of carbon dioxide and oxygen was 490-590 and 19-208ppm respectively. Also, the highest and lowest levels of carbon dioxide were 584.56±6.36 and 453.94±77.7 ppm in wet water camp and S10 wells (P 0.05) in the same order. Conclusion:Pearson and Spearman coefficient analysis showed no significant correlation between temperature, humidity, oxygen and carbon dioxide. According to the results, the concentration of carbon dioxide in different areas of the oil field of Yadavaran was acceptable.